Principles of Cost Accounting: managerial Applications - Rayburn, Gayle L. (Illinois, USA Richard D. Irwin Inc., 1983)
This textbook has been written to allow instructors flexibility in the chapter materials presented. The first 11 chapters discuss cost accounting principles and concepts concerned with the collection of cost, which is an influencing factor in such managerial decisions as determining sales price.The last part of the book emphasized the application of cost principles and quantitative tools to decision making.
includes index
jbi, 14/03/2018
Loans
Keywords: Cost Accounting; Mangerial accounting